NILAI LOKALITAS ORANG BAJO DALAM CERPEN “LANDO” (Locality Value of Bajonese in “Lando” Short Story) - Heksa Biopsi Puji Hastuti (Kantor Bahasa Provinsi Sulawesi Tenggara, 2012)
Short story entitled “Lando” written by Ucu Agustin tells the story about two kids who live far away from their ancestor‟s hometown. The author raisedlocality of Bajonese as the color of her short story. This paper discusses localityvalue of Bajonese conteined therein. The approach used in the discussion is structuralism with reference to Francois-Robert Zacot‟s ethnographic research result at the phase of understanding locality value in the story. From the discussion it is known that the author explores the nuances of bajo by using dictions from Bajo language. The value of Bajonese locality is represented with the inclusion of Bajo culture either in the form of myths and beliefs and way of Bajo people life that cannot be separated from sea. Even readers who have not learned at all about bajo can acquire imagery of Bajonese by reading “Lando” short story. Cerpen “Lando” karya Ucu Agustin berkisah tentang dua anak Bajo yang hidup jauh dari kampung halaman leluhur mereka. Pengarang mengangkat nuansa lokal orang Bajo sebagai warna untuk cerpennya. Tulisan ini membahas tentang nilai lokalitas orang Bajo yang termuat di dalamnya. Pendekatan yang digunakan ialah pendekatan struktural dengan mengacu pada hasil penelitian etnografi Francois-Robert Zacot pada tahap pemahaman nilai lokalitas orang Bajo dalam cerpen ini. Dari pembahasan diketahui bahwa pengarang mengeksplorasi nuansa Bajo dengan penggunaan beberapa kosa kata daribahasa Bajo. Nilai lokalitas orang Bajo direpresentasikan dengandimasukkannya budaya Bajo baik berupa mitos dan kepercayaan maupun cara hidup mereka yang tidak lepas dari laut. Pembaca yang belum mengetahui samasekali tentang orang Bajo, bisa memperoleh gambaran yang cukup denganmembaca cerpen “Lando”.